2000
DOI: 10.1055/s-2000-10106
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen elastischer Lumbal-Stützgurte auf den Effekt eines Muskeltrainingsprogrammes für Patienten mit chronischen Rückenschmerzen

Abstract: The effectiveness of the muscle strengthening program for patients with low back pain could be improved significantly by means of the elastic lumbar belt as an applicable therapy instrument in the functional rehabilitation of spinal injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…The papers of Hsieh and Pope, two papers of Dalichau and two of van Poppel appeared to be reports of the same study. Based on titles, subject headings, abstracts and journal types, eight articles were included (Dalichau 2000;Doran 1975;Gibson 2002;Hsieh 1992;Million 1981;Valle-Jones 1992;Walsh 1990). Screening references of articles and reviews resulted in four additional studies (Alexander 1995;Coxhead 1981;Kraus 2002;Reddell 1992).…”
Section: Results Of Literature Search and Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The papers of Hsieh and Pope, two papers of Dalichau and two of van Poppel appeared to be reports of the same study. Based on titles, subject headings, abstracts and journal types, eight articles were included (Dalichau 2000;Doran 1975;Gibson 2002;Hsieh 1992;Million 1981;Valle-Jones 1992;Walsh 1990). Screening references of articles and reviews resulted in four additional studies (Alexander 1995;Coxhead 1981;Kraus 2002;Reddell 1992).…”
Section: Results Of Literature Search and Study Selectionmentioning
confidence: 99%
“…In summary, seven preventive studies (Alexander 1995;Gaber 1999;Kraus 2002;Reddell 1992;Roelofs 2007;Walsh 1990) and eight treatment studies (Coxhead 1981;Dalichau 2000;Doran 1975;Gibson 2002;Hsieh 1992;Million 1981;Penrose 1991;Valle-Jones 1992) were included. Since the last review, two new studies on prevention (Kraus 2002;Roelofs 2007) and two new studies on treatment (Dalichau 2000;Gibson 2002) were found.…”
Section: Results Of Literature Search and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vorrangiges Ziel jeder therapeutischen Intervention bei chronifizierten spinalen Beschwerden ist die Schmerzreduktion und konsekutiv die Verringerung der Funktionseinschränkungen bei Aktivitäten des täglichen Lebens (ADL) [26,27]. Somit lässt sich für alle eingesetzten Behandlungsverfahren in der vorliegenden Studie a priori ein positiver Wirknachweis konstatieren.…”
Section: Diskussionunclassified